PENGARUH PENGGUNAAN MEDIA BINGKAI 10 TERHADAP PEMAHAMAN PART-PART-WHOLE PADA ANAK USIA 6-7 TAHUN (STUDY EKSPERIMEN DI BKB PAUD ANGGREK KELURAHAN MUNJUL, KECAMATAN CIPAYUNG, JAKARTA TIMUR) - Kartika Sari, Intani Dewi; Hapidin, Hapidin (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2021)
This study aims to obtain empirical data on the effect of Ten Frame Media usedto understand Part-part-whole in 6-7 Years old at in Munjul Village, Cipayung Subdistrict, East Jakarta. The method used is kuantitatif research with experiment approach and the research design is True Experimental with Two Group Pre-test and Post-test Design (technique of pre-test and post-test with two groups randomized). The population in this study were all students aged 6-7 years which is a group of early childhood in the Munjul Village. The sample in this study is children aged 6- 7 years in early childhood education for School Readiness Group (KeMaS) with a sample of 15 children in the experimental group and 15 children in the control group, which was taken by using simple random cluster technique. Data collection tools of Variable Y (Part-part-whole Understanding) is done using techniques of observation checklist. The analysis technique used is the t-test for small samples are not correlated. Based on the results of hypothesis testing using t-test is obtained price thitung1 = 22, 5 (comparative test of pre-post test Experimental Group), thitung2 = 8, 90 (Comparative test of pre-post test control group), and thitung3 = 30, 79 (Comparative test of post-post-test Experiment- Control Group), a price table = 1, 70, and dk = 28 at the significant level α = 0.05. From these results it can be concluded that thitung> ttable, so this study reject H0 (Zero Hypothetical) and receiving Ha (Alternative Hypothesis). This study therefore implies that the use of 10 frames media significant effect on the understanding part-part-whole in children aged 6-7 years. The more often a child at the age of 6-7 years using the media frame 10, then the better the understanding of the part-part-whole.